Vacuum-induced degradation of 2D perovskites - Hofstetter, Yvonne J.; García-Benito, Inés; Paulus, Fabian; Orlandi, Simonetta; Grancini, Giulia; Vaynzof, Yana (Frontiers in Chemistry, 2020)
Two-dimensional (2D) hybrid organic-inorganic perovskites have recently attracted the attention of the scientific community due to their exciting optical and electronic properties as well as enhanced stability upon exposure to environmental factors. In this work, we investigate 2D perovskite layers with a range of organic cations and report on the Achilles heel of these materials - their significant degradation upon exposure to vacuum. We demonstrate that vacuum exposure induces the formation of a metallic lead species, accompanied by a loss of the organic cation from the perovskite. We investigate the dynamics of this reaction, as well as the influence of other factors, such as X-ray irradiation. Furthermore, we characterize the effect of degradation on the microstructure of the 2D layers. Our study highlights that despite earlier reports, 2D perovskites may exhibit instabilities, the chemistry of which should be identified and investigated in order to develop suitable mitigation strategies.
Gesehen am 23.03.2020